KEPUASAN MAHASISWA TERHADAP MUTU PELAYANAN STAF ADMINISTRASI KEUANGAN DI AKADEMI KEPERAWATAN DIRGAHAYU SAMARINDA - Yovita Erin Sastrini (LPPM University 17 Agustus 1945 Samarinda, 2018)
ABSTRACTThe purpose of the study was to reveal student satisfaction with total service, service dimensions, and items of service for administrative staff in the financial section of Akper Dirgahayu. This research is a quantitative descriptive study that describes student satisfaction with financial administration services. The study was conducted from November and December 2016 at the Campus of Nursing Academy in Samarinda.The research subjects were second-level students, amounting to 185 people, and the object of the study was student satisfaction with the quality of financial part administration services at Akper Dirgahayu. Data collection uses a Likert 4 choice satisfaction questionnaire developed from 5 dimensions of service quality, namely tangibles, responsiveness, reliability, empathy, and assurance. Analysis of data describing student satisfaction with service is carried out using the Student Satisfaction Index (IKM) and percentage distribution table.The results showed that (1) student satisfaction with the service of the administrative staff of the financial section of Akper Dirgahayu belonged to the category of satisfaction, the student satisfaction index value (IKM) for the total service was 68.90 (classified as satisfied) and about 70 percent of students had satisfaction scores classified as categories satisfied and very satisfied; (2) Satisfaction with all dimensions of service and for all service items also has the value of SMIs classified as satisfied; and (3) there are a number of items including potential perceived dissatisfaction by students. These items are friendliness, ease of meeting officers, alertness asking for needs, speed of service, convenience / suitability of service procedures, officer justice, willingness of officers to help difficulties, accuracy of officer appointments, every service request is always fulfilled, and the ability of officers to provide solutions. Each of these items was perceived as dissatisfied and very dissatisfied with more than 30 percent of students.